Cerebral Abscess In A Child With Unknown Origin Of Infection: A Case Report - Arafat Husain, Syekh Ahmad; Alloyna, Dhyka; Irsyad, Muhammad Ari; Tala, Ihsan Z; Arsyad, Abdurrahman Mousa (Talenta Universitas Sumatera Utara, 2023)
Introduction: The incidence of brain abscesses is higher in developing countries. The classic triad of fever, headache, and focal neurological signs was seen in 9â€“28% of the pediatric cases. Brain abscesses occur infrequently with potentially life-threatening conditions. Case Report: The patientÂ was a child 1 year 8 months old with a main complaint of weakness in the left arm and leg progressively for one month. She had a local seizure on her left arm and leg one month before admission with a duration of 30 minutes. She was irritable for the last two weeks. The strength of the upper and lower extremities was 3 respectively. The physiology reflex was hyper-reflex on the upper and lower extremities. A Head non-contrast CT scan showed a hypodense lesion on the right parietal with a perifocal edema lesion. A head contrast CT scan showed a hypodense lesion on the right parietal with ring enhancement measuring approximately 6,2 cm x 4,5 cm. Craniotomy evacuation abscess with near total capsulectomy was done on initial and capsule resection was done. Discussion: Brain abscess is a focal pyogenic infection of the brain parenchyma, and the frontotemporal lobe is the most common site of brain abscess, followed by frontal-parietal, parietal, occipital lobes, and cerebellar. The most common risk factors that predispose a child to the formation of a brain abscess include congenital heart disease, sinus and otogenic infections, and poor dental hygiene. The triad of brain abscess, including headache, fever, and neurological symptoms is only present in (15%) of the cases reported. Medical treatment is recommended in patients without increased intracranial pressure, with symptoms of less than 1 week long and abscess of less than 2 cm seen in tomography. The suggested time of treatment is between 6 and 8 weeks with intravenously administered antibiotics. A full recovery rate from the infection of about 60â€“70% is reported in the case of early diagnosis and proper therapy Conclusion: Cerebral abscess in pediatrics with unknown origin of infection may happen in 12%. Early diagnosis and treatment of pediatric cerebral abscesses can reduce morbidity and mortality rates. A broadspectrum antibiotic is an optimal treatment in the postoperative evacuation of cerebral abscess cases with unknown origin infection.